Occurrence of infectious and parasitary diseases in goats and sheep in the metropolitan region of São Luís, State of Maranhão, Brazil (Research, Society and Development, 2020)
The objective of this work was to verify the occurrence of infectious and parasitic diseases in goats and sheep in the metropolitan region of São Luís, state of Maranhão. For the detection of Maedi-Visna anti-virus antibodies and for the diagnosis of caprine arthritis encephalitis, the agar gel immunodiffusion technique (IDGA) was used. To identify endoparasites, the McMaster technique was used. The collection of ectoparasites was performed by inspection and palpation in the animals, with the ticks subsequently examined in a stereomicroscope and identified through a dichotomous key; lice, on the other hand, were mounted between a blade and a coverslip. The analyzes revealed the prevalence of Maedi-Visna in 1.02% of the 98 sheep sampled, and antibodies against the Caprine Arthritis Encephalitis virus were found in 2.29% of the goat herd (87). Among the 170 fecal samples of goats and sheep examined, it was found that 84.1% contained Strongyloidea and Moniezia sp. and oocysts of Eimeria sp. In only 6.9% of the 87 inspected goats, an ectoparasite specimen was found. The species of lice identified in this study were Bovicola caprae and Linognathus africanus. The tick species identified as parasitic on goats was Rhipicephalus (Boophilus) microplus. It was concluded that infection with Maedi Visna, Arthritis, Encephalitis Caprina, ectoparasitoses and endoparasitoses are present in sheep and goats in the metropolitan region of São Luís, emphasizing the importance of implementing public policies for the prevention and control of these diseases.